On Secret Service : A Novel - Jakes, John (London Timewarner, 2000)
A novel based around the exploits of various spies during the American Civil War. Lon supports the north, works for the War Department and is offered a job in the National Detective Police force. Margaret supports the south and works for her father until her outspokenness lands her in prison.
Keywords: United States -- Secret Services